O gerencialismo na educação pública: a implementação do Sistema da Gestão Integrado (SGI) na rede municipal de Campina Grande-PB - Medeiros, Sonayra da Silva (2013)
This dissertation results of a research in four municipal schools in Campina Grande/PB, objecting to analyze, in teaching municipal net, the management model of public school, specifically, the Integrated Management System (IMS) and their implementation process, by the understanding of managements and teachers. As theoretician and methodological proceedings, we realized conceptual deepening, documental analyzes, interviews with managements and we applied questionnaires with the teachers of chosen schools. In this research, we analyzed the IMS inserted in the context of changes and redefinition of State function, considering the Reform of State Apparatus in 1990 s and the public management administration. We adopted, yet, as theoretician support, the conception of amplified State of Gramsci, actual studies about New Liberalism of Third Way and their repercussions in educational politics, with the new configuration of civil society and the management function in public education. In this study, that foments the discussion about the interferences of management model in public school administration, we could certify, in general, an acceptation of IMS, for managements and teachers, understand it an efficient instrument to organization of pedagogical work. Which concerns, most specifically, to teachers, we observed some restrictions for this management model, deriving for work intensification that it causes. In a short synthesis, we consider that IMS constitutes in a big challenge for all that worries about for management democratization in school ambit.